Enhancing Family Nutrition and Economy by Cultivating Catfish in Aquaponic Systems to Optimise Narrow Land Space - Soebroto, Arief Andy; Suryanto Hertika, Asus Maizar; Nurlaelih, Euis Elih; Baghaz, Renanda DSP; Alfarisi, Muhammad Asnin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2024)
The MMD 1000 Village Strategic Community Service Grant Program aims to address the issues that the village community is currently facing, such as the low level of community participation in PKK activities, the need to improve the nutrition of low-income families, and the underutilization of narrow yards. So that through the MMD 1000 Village Strategic Community Service Grant Programme activities, this will offer solutions to these problems, including outreach and demonstration plots along with the assistance of aquaponic cultivation systems. The methods that will be applied to this activity include the following: 1) providing understanding to community leaders and target audiences, especially activity partners; 2). Counselling and training to increase knowledge about the implementation of an appropriate aquaponic cultivation system, 3). Direct practice or application of the aquaponic cultivation system, including assembling the design of aquaponics tools, setting tools and tanks, water preparation and monitoring water quality, stocking fish seeds, planting vegetable seeds, and raising fish and vegetables together 4). Evaluation to monitor success in implementing activities, 5). Evaluate the impact of activities directly on increasing fish and vegetable consumption and the impact on the family economy through fish and vegetable production. This activity increases the community's ability to manage narrow land by implementing an aquaponic system, which has an impact on improving family nutritional welfare and increasing economic income and is expected to be implemented by the wider community in Dawuhan Village and other villages in Malang Regency.